1998
DOI: 10.7326/0003-4819-128-12_part_1-199806150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Use of Enalapril To Attenuate Decline in Renal Function in Normotensive, Normoalbuminuric Patients with Type 2 Diabetes Mellitus

Abstract: Enalapril attenuated the decline in renal function and reduced the extent of albuminuria in normotensive, normoalbuminuric patients with type 2 diabetes. Further research is needed to determine whether this treatment forestalls the development of overt nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
0
10

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(178 citation statements)
references
References 23 publications
3
165
0
10
Order By: Relevance
“…This is not the case in type 2 diabetic patients treated with ACEI, in whom our results show a better prognosis of renal function than was seen in patients treated with other antihypertensives. This finding is in agreement with previous evidences about favorable effects of ACEI on prevention of CKD in type 2 diabetes (30).…”
Section: Discussionsupporting
confidence: 83%
“…This is not the case in type 2 diabetic patients treated with ACEI, in whom our results show a better prognosis of renal function than was seen in patients treated with other antihypertensives. This finding is in agreement with previous evidences about favorable effects of ACEI on prevention of CKD in type 2 diabetes (30).…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless there is also recent evidence for additional BP-independent renoprotection by angiotensin receptor blocking agents and advanced (100,101) and early nephropathy of type 2 diabetes (31,102). In less rigorous trials, similar renoprotection, in part BP-independent, has previously also been shown for ACE inhibitors (103,104), including a study documenting benefit on renal histology (105). Attempts at achieving these BP targets must be tempered by the observation that in the IDNT trial (101) the renal risk increased progressively as BP in the orthostatic position was lower, possibly because of injury from intermittent renal underperfusion potentially explained by reduced ischemia tolerance of the diabetic kidney (106).…”
Section: Prevention Of Progressionmentioning
confidence: 98%
“…The benefit of blocking the RAAS with ACEi and ARBs in a variety of kidney diseases, including DN, is now well established. [63][64][65][66][67][68][69][70] However, such treatment does not completely abrogate the progression of kidney disease. [69][70][71] This partial response has been attributed in part to feedback effects, such as angiotensin-escape and aldosteroneescape.…”
Section: Blood Pressure Controlmentioning
confidence: 99%